Histopathological study of Corydoras micracanthus (Siluriformes: Callichthyidae) parasitized by the nematode Procamallanus (Spirocamallanus) pintoi (Camallanidae) from Lesser River, northwestern Argentina, South America - Ailan Choke, Lorena Gisela (2019)
The nematode parasites can cause mechanical injuries such as irritation or atrophy of tissue and occlusions of the digestive tract, blood vessels or other ducts in their hosts. Some species belonging to the family Camallanidae have been the focus of histopathological studies because they lacerate the host´s intestinal wall with their buccal capsule. In this study, we describe the histopathological effects produced by Procamallanus (Spirocamallanus) pintoi in the small fish Corydoras micracanthus from Lesser River, in the northwest of Argentina, South America. The samples were processed with routine histology techniques. At light microscopy, specimens of P. (S.) pintoi were observed occupying the lumen of the gut. The histopathological sections revealed damage to the host intestine with the total destruction of the mucosa and submucosa, observed mainly in the region which is surrounding the buccal capsule of parasites. Moreover, an inflammatory reaction was observed with lymphatic accumulations in the affected tissue. This kind of degenerative and necrotic changes in the mucosa could affect negatively the absorption function of the host intestine, which may have adverse effects of the health status of fish. The present study provides the firs data about the histopathological effects of P. (S.) pintoi in C. micracanthus.